Analysis of Subsidies for Services The Case of Export Subsidies - Geloso Grosso, Massimo (OECD Trade Policy Papers, 2008)
This study presents an exploratory analysis of export subsidies in the services field. It draws from a variety of sources in an effort to provide insights into the characteristics and use of these measures. The report, while not generating accurate measures of the extent and effects of export subsidies for services, provides evidence that these measures are used by many countries in the developed and developing worlds to support a wide range of services sectors. The analysis also indicates that broadly speaking the definitions contained in the WTO Agreement on Subsidies and Countervailing Measures (ASCM) are relevant for services. The most important types of export support appear to be direct tax incentives, particularly profit tax exemptions or reductions. Based on the detailed analysis of export subsidies for services, the study then discusses some possible elements of a definition of these measures